The Effect of Experimental Methods on Students' Cognitive Learning Outcomes in Elementary Schools: Pengaruh Metode Eksperimen Terhadap Hasil Belajar Kognitif Siswa di Sekolah Dasar - Artha, Elsa Anggun Dwi; Setiyawati, Enik (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the effect of the Experimental Method on cognitive learning outcomes in science learning at SDN Sawohan 1. The method used in this study is a quasi-experimental quantitative type of experiment with a Nonequivalent Control Group Design. Sampling using saturated sampling technique. The instrument used is a written test which is made according to the indicators of cognitive learning outcomes. Data collection in this research is by using pretest and posttest sheets. Data were analyzed using t-test and eta squared test. The results of the hypothesis test of the control class and the experimental class are 8.39 > 2.01 then H0 is rejected and H1 is accepted. So it can be seen that there is an effect of the experimental method to improve cognitive learning outcomes. In addition, the eta squared test results obtained a value of 0.08 with eta square criteria < 0.014, the result is that the experimental method has a moderate effect on improving students' cognitive learning outcomes in elementary schools